The Relationship Between Physical Activity And Body Mass Index In Elementary School’s Students - Made Kurnia Widiastuti Giri; Ketut Parining; Putu Ayu Aprilia Saraswati; Anak Agung Ayu Mutiara Parameswari; I Gede Kawihana; Ayu Komang Awidya Maha Dewi; Desak Putu Ramita Pratiwi (Universitas Pendidikan Ganesha, 2026)
Physical activity is essential for maintaining energy balance and preventing obesity, while Body Mass Index (BMI) serves as a simple indicator of nutritional status in school-aged children. This study aimed to examine the relationship between physical activity and BMI among sixth-grade students. An observational analytic design with a cross-sectional approach was applied, involving 60 students in SDN 3 Seririt elementary school, who met the inclusion criteria. Physical activity was assessed using a questionnaire, and BMI was calculated from weight and height measurements. Data were analyzed with the Spearman Rank test. Results showed that 46.67% of students had moderate physical activity, while BMI distribution included 60% normal, 5% underweight, 13.33% overweight, 20% obese, and 1.67% severe obesity. Statistical analysis revealed a p-value of 0.0033 (p < 0.05) with a weak negative correlation (r = -0.276). These findings indicate a significant relationship between physical activity and BMI in the study population.